Predictors of 6-month health utility outcomes in survivors of acute respiratory distress syndrome. Issue 4 (20th July 2016) - Brown, Samuel M; Wilson, Emily; Presson, Angela P; Zhang, Chong; Dinglas, Victor D; Greene, Tom; Hopkins, Ramona O; Needham, Dale M
Abstract : Background: With improving short-term mortality in acute respiratory distress syndrome (ARDS), understanding and improving quality of life (QOL) outcomes in ARDS survivors is a clinical and research priority. We sought to identify variables associated with QOL, as measured by the EQ-5D health utility score, after ARDS using contemporary data science methods. Methods: Analysis of prospectively acquired baseline variables and 6-month EQ-5D health utility scores for adults with ARDS enrolled in the ARDS Network Long-Term Outcomes Study (ALTOS). Penalised regression identified predictors of health utility, with results validated using 10-fold cross-validation. Results: Among 616 ARDS survivors, several predictors were associated with 6-month EQ-5D utility scores, including two lifestyle factors. Specifically, older age, female sex, Hispanic/Latino ethnicity, current smoking and higher body mass index were associated with lower EQ-5D utilities, while living at home without assistance at baseline and AIDS were associated with higher EQ-5D utilities in ARDS survivors. No acute illness variables were associated with EQ-5D utility. Conclusions: Acute illness variables do not appear to be associated with postdischarge QOL among ARDS survivors. Functional independence and lifestyle factors, such as obesity and tobacco smoking, were associated with worse QOL. Future analyses of postdischarge health utility among ARDS survivors should incorporate measures of demographics and functional independence at baseline. Trial registration numbers: NCT00719446 (ALTOS), NCT00434993 (ALTA), NCT00609180 (EDEN/OMEGA), and NCT00883948 (EDEN); Post-results.